Demokrasi pancasila dan tantangan partisipasi politik generasi z di Indonesia - fares, abid al (Maliki Interdisciplinary Journal, 2026)
Pancasila democracy, as a political system rooted in the noble values of the Indonesian nation, continues to face serious challenges amid the tide of social change driven by globalization and the digital revolution. Generation Z, born between 1997 and 2012, is now the largest voter group in Indonesian elections, including the 2024 Presidential Election; however, their political participation still reveals a significant gap between potential and actual engagement. This article aims to analyze the relationship between the democratic values of Pancasila and the dynamics of Generation Z’s political participation, as well as to identify existing barriers and opportunities. Through a literature review of six relevant academic sources, this study finds that low political literacy, the negative influence of social media, the filter bubble phenomenon, and political apathy are the primary barriers. On the other hand, easy access to digital information, the relevance of contemporary issues, and the potential for technology-based political education open strategic avenues for increasing Generation Z’s engagement. This article argues that the internalization of Pancasila democratic values through character education, the constructive use of digital platforms, and the strengthening of political literacy are the integrative steps needed for Generation Z to serve as responsible agents of democratic change with a national perspective.